2012
DOI: 10.1111/j.1744-7917.2012.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Population specific fitness response of Drosophila subobscura to lead pollution

Abstract: Differences in heavy metal tolerance among separate populations of the same species have often been interpreted as local adaptation. Persistence of differences after removing the stressor indicates that mechanisms responsible for the increased tolerance were genetically determined. Drosophila subobscura Collin (Diptera: Drosophilidae) populations were sampled from two localities with different history of heavy metal pollution, and reared for eight generations in the laboratory on a standard medium and on media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…It shows that for all groups, the presence of lead was an environment with a low level of stress (Lopes et al 2004(Lopes et al , 2006. These results are in agreement with Kenig et al (2013) where authors found no intergenerational differences in viability between the groups from analysed populations of D. subobscura reared on different lead concentrations, which indicates that a low concentration is not sufficient to be a stress agent. Despite the fact that lead has no significant influence on viability in D. subobscura, our results of egg-to-adult viability showed significant differences between the types of crosses, such that the viability of intraline crosses was reduced on both media.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…It shows that for all groups, the presence of lead was an environment with a low level of stress (Lopes et al 2004(Lopes et al , 2006. These results are in agreement with Kenig et al (2013) where authors found no intergenerational differences in viability between the groups from analysed populations of D. subobscura reared on different lead concentrations, which indicates that a low concentration is not sufficient to be a stress agent. Despite the fact that lead has no significant influence on viability in D. subobscura, our results of egg-to-adult viability showed significant differences between the types of crosses, such that the viability of intraline crosses was reduced on both media.…”
Section: Discussionsupporting
confidence: 94%
“…Development time showed significant increase and the same pattern of response in all groups reared under lead contamination. The obtained result is not in agreement with some previously reported data (Shirley and Sibly 1999;Kenig et al 2013) which suggests that individuals exposed to lead pollution during several generations showed faster development compared to those reared on the standard medium, explaining that shorter development time is an advantage, at least, for Drosophila species, because the larval stage is less exposed to the stressful environment. Wu et al (2006) detected that the total duration of the development from larva to adult of Boettcherisca peregrine was (Schmidt et al 1991), Lymantria dispar (Gintenreiter et al 1993), Chironmus riparius (McCadhon and Pascoe 1991) and Oncopeltus fasciatus (Cervera et al 2004).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…They are genetically diverse (according to putatively adaptive polymorphism), even on a small geographic scale, with frequently strong and unpredictable consequences of inter-population hybridization (KURBALIJA et al, 2010). There is also an indication of local genetic adaptation to heavy metal pollution and population specific fitness response to heavy metal pollution (KENIG et al, 2013). In recent years, geometric morphometric analysis of D. subobscura wings proved to be useful model for genetic and evolution studies and evaluation of number of factors, including genetic and environmental stress (HUEY et al, 2000;GILCHRIST and HUEY, 2004;SANTOS et al, 2004SANTOS et al, , 2005KURBALIJA NOVIČIĆ et al, 2012, PATENKOVIC et al, 2015.…”
mentioning
confidence: 99%